2007
DOI: 10.1038/nrg2218
|View full text |Cite
|
Sign up to set email alerts
|

Histone lysine demethylases: emerging roles in development, physiology and disease

Abstract: The discovery of an increasing number of histone demethylases has highlighted the dynamic nature of the regulation of histone methylation, a key chromatin modification that is involved in eukaryotic genome and gene regulation. A flurry of recent studies has offered glimpses into the specific biological roles of these enzymes and their potential connections to human diseases. These advances have also catalysed a resurgence of interest in epigenetic regulators as potential therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
441
0
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(459 citation statements)
references
References 61 publications
6
441
0
12
Order By: Relevance
“…Histone demethylases can reverse the effects of methyltransferases by removing methyl groups at specific lysine residues on histones (Shi, 2007), but their role in adult stem cells is still relatively unexplored. However, a few key examples highlight potentially critical functions for these molecules in stem cell maintenance during aging and illustrate the dynamic nature of chromatin changes.…”
Section: Histone Demethylases As Regulators Of Reversible Chromatin Smentioning
confidence: 99%
“…Histone demethylases can reverse the effects of methyltransferases by removing methyl groups at specific lysine residues on histones (Shi, 2007), but their role in adult stem cells is still relatively unexplored. However, a few key examples highlight potentially critical functions for these molecules in stem cell maintenance during aging and illustrate the dynamic nature of chromatin changes.…”
Section: Histone Demethylases As Regulators Of Reversible Chromatin Smentioning
confidence: 99%
“…10 Vitamin C is also an important cofactor in several enzymatic reactions such as histone demethylases and prolylhydroxylases. 11 Recent studies have demonstrated that vitamin C supplementation produces important effects on stem cell generation, proliferation and differentiation. 12 It was reported that the supplementation of vitamin C with an appropriate dose in culture medium could increase the efficiency of induced pluripotent stem cell generation from human somatic cells, 13 enhance the expansion and osteogenic differentiation of bone marrow-derived mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Lysine acetylation and methylation are both reversible processes thanks to the activities of histone deacetylases and recently discovered demethylases [1,4]. Both of these enzyme families are implicated in a range of developmental and physiologic pathways as well as in malignancy [1,5,6].…”
Section: Introductionmentioning
confidence: 99%